“The Ghost Language Which Passes between the Generations”: Transgenerational Memories and Limit-Case Narratives in Lisa Appignanesi’s Losing the Dead and The Memory Man - Silvia Pellicer-Ortín (Humanities, 2020)
This article aims to uncover the tensions and connections between Lisa Appignanesi’s autobiographical work Losing the Dead (1999) and her novel The Memory Man (2004) and to point out that, in spite of belonging to different genres, they share several formal, thematic, and structural features. By applying close-reading and narratological tools and drawing on relevant theories within Trauma, Memory, and Holocaust Studies, I would like to demonstrate that both works can be defined as limit-case narratives on the grounds that they blur literary genres, fuse testimonial and narrative layers, include metatextual references to memory and trauma, and represent and perform the transgenerational encounter with traumatic memories. Moreover, Appignanesi’s creations will be contextualised within the trend of hybrid life-writing narratives developed by contemporary British-Jewish women writers. Accordingly, these authors are contributing to the expansion of innovative liminal autobiographical and fictional practices that try to represent what it means to be a Jew, a migrant, and an inheritor of traumatic experiences in the post-Holocaust world. Finally, I launch a further reflection on the generic hybridisation characterising those contemporary narratives based on the negotiation of transgenerational memories, which will be read as a fruitful strategy to problematize the conflicts created when the representation of the self and (family) trauma overlap.